Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2007
DOI: 10.1128/jcm.00655-07
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring of Polyomavirus BK Virus Viruria and Viremia in Renal Allograft Recipients by Use of a Quantitative Real-Time PCR Assay: One-Year Prospective Study

Abstract: We have developed a real-time quantitative PCR (rt-QPCR) assay to detect and kinetically monitor BK virus viruria and viremia in renal transplant recipients (RTRs). A total of 607 urine and 223 plasma samples were collected from 203 individuals including those with BK virus-associated nephropathy (BKVAN) (n ‫؍‬ 8), those undergoing routine posttransplant surveillance (SV) (n ‫؍‬ 155), those with nontransplant chronic kidney disease (NT-CKD) (n ‫؍‬ 20), and healthy living kidney donors (LD) (n ‫؍‬ 20). The rt-Q… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
48
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 64 publications
(54 citation statements)
references
References 32 publications
3
48
1
Order By: Relevance
“…Monitoring of BKV viruria is noninvasive and can be informative, as a high level of BK viruria usually precedes viremia and potential nephropathy by 4 to 12 weeks (1,27). Even though a cutoff value or a positive predictive value is hard to define, a viruria level of Ͼ7 log 10 should alert clinicians and indicate the need to increase surveillance of viremia (28). Regarding the assessment of BKVL in the blood compartment, validation of WB as an appropriate matrix was recently carried out (29), but no study thus far has endeavored to contrast plasma and WB samples for BKVL determination.…”
Section: Discussionmentioning
confidence: 99%
“…Monitoring of BKV viruria is noninvasive and can be informative, as a high level of BK viruria usually precedes viremia and potential nephropathy by 4 to 12 weeks (1,27). Even though a cutoff value or a positive predictive value is hard to define, a viruria level of Ͼ7 log 10 should alert clinicians and indicate the need to increase surveillance of viremia (28). Regarding the assessment of BKVL in the blood compartment, validation of WB as an appropriate matrix was recently carried out (29), but no study thus far has endeavored to contrast plasma and WB samples for BKVL determination.…”
Section: Discussionmentioning
confidence: 99%
“…24 The high level of creatinine in kidney allograft recipients, reported from different regions, is the first indication of suspicious involvement of this viral infection in nephropathy, which calls for measuring viral loads in urine and plasma of such patients. 9,25,26 The natural history of BK polyomavirus infection and reactivation in kidney transplant patients is poorly understood. However, some evidence indicates that transplant patients with BKVAN had frequent rearrangements in the NCCR genomic region of BK polyomavirus isolated from either circulatory specimens including blood, serum, and plasma or from their urogenital region such as kidney biopsy specimens and urine.…”
Section: Discussionmentioning
confidence: 99%
“…Recent studies showed that BK polyomavirus is associated with nephropathy in 8% kidney allograft recipients. [7][8][9] Different studies suggest that prospective monitoring of patients who are at risk for BKVAN may help to identify active infection in those who may have borderline deteriorated kidney function. 7,9,10 Control of BK polyomavirus replication and prevention of BKVAN is possible by tapering the dose of immunosuppressive drugs.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations